Recreating heritage in Barelang zone, Indonesia - Delima, Sylvia Prisca; Wirutomo, Paulus; Moersidik, Setyo Sarwanto; Alamsyah, Abimanyu Takdir (Kasetsart Journal of Social Sciences, 2021)
Barelang zone, Indonesia, has been intended as a showcase of the physical and social development process as well as a modern heritage and archive site. This article employs a case study method to seek whether it has achieved its social function as a modern heritage site. The findings show that infrastructure development is considered as an effort to build future heritage where cultural transformation has deliberately taken the material culture into account; the preservation of socially perceived images and their creative use may lead to heritage creation, and it may give a boost towards a sense of national pride; it provides alternative sources of education materials and sustainable development archives. However, dynamic characteristics of ongoing progress, visual products, and their narratives attached to infrastructure as public spaces have not yet acted as archive sites that preserve knowledge and lessons learned that could be used for educational tools that benefit sustainable development.